Practical Lessons in Public Health Program Implementation: Perspectives from the Field. Issue 4 (2nd April 2020) - Johnson, Katherine J.; Alexander, Cassie J.; Baron, Sarah; Collins, Amy; Corran, Becky; Dick, Jacqueline A.; Krouse, Rhonna; Salis, Andrea; Schmidt, Kaysie; Smith, Lillian U.; Srivastava, Anuradha; Tupala, Kay
ABSTRACT: Over the past 15 years, significant advances have been made in public health education in the United States, creating new opportunities for community colleges, especially in terms of clarifying career and general transfer pathways for students. In 2014, a national taskforce published two curricular models for public health education in community colleges. One model was an associate degree for academic transfer to a baccalaureate program and the other an applied degree or applied certificate for entry into the workforce. This paper provides perspectives from eight diverse institutions that have developed public health programming based on these curricular models.